PEMBELAJARAN MATA KULIAH BAHASA INDONESIA BERBASIS KARAKTER UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM MERDEKA DI PERGURUAN TINGGI - Irianto (Manajemen Pendidikan Program Doktor, 2023)
The purpose of this study is to determine the implementation of character education integration into Indonesian language lectures based on the independent curriculum and also to find out the obstacles and problems in the implementation of character education integration in Indonesian language lectures based on the independent curriculum. the research in this journal is descriptive qualitative research. Descriptive qualitative research is a research procedure that produces descriptive data from people and behavior observed in the form of written or spoken language. The research was conducted on STTI Bontang students majoring in mechanical engineering and chemical engineering semester 2, using data collection interviews via google from.1. Description of Research Results Based on the results of interview research on STTI Bontang semester 2 students and mataram university, the research results are: What are the obstacles in character-based Indonesian language learning that are not running properly. the obstacles are still from students who are active when learning Indonesian language courses to liven up the interactive classroom atmosphere and the Implementation of the Merdeka Curriculum even though it has been running smoothly in the past few months, there are still several obstacles such as, among others, lack of experience with learning independence, limited references and uneven access to learning, time management. The concept of learning Indonesian language courses in supporting an independent curriculum in higher education has the concept of how students have a deeper character to participate in supporting an independent curriculum and during the lecture process students are taught, more active and effective in lectures. Thus students are expected to support an independent curriculum in higher education. The independent study program is implemented by giving freedom to educational institutions, including students, to identify topics, interests and desire to learn. They are also free to determine the learning methods that suit their needs. Merdeka Belajar - The Independent Campus Policy aims at the